Application Design for Recording Financial Statements - S Surtikanti; L Lutfiah; I Andaresya; I Febriani (Universitas Komputer Indonesia, 2021)
The development of information technology users requires applications to organize the recording and presentation of financial report data more easily and accurately. The current financial statements are not only by companies but also by Micro Small and Medium Enterprises (MSMEs). Besides, the public also uses them to manage their financial records. The purpose of this research is to develop accounting applications that have been circulating today to support financial statements to ensure data security. This research used a descriptive qualitative method to collect data in accordance with field facts. The population of this research is students of Universitas Komputer Indonesia who learn to use accurate applications because accurately studied by accounting students, the sample is students majoring in accounting. Sample techniques used purposive sampling, where respondents will be selected according to the criteria. Data collection through questionnaires were distributed online to obtain data in accordance with field facts. This study shows that the development of accounting applications supports the recording of financial statements in maintaining the security of existing data in financial statements. It impacts MSMEs who want to store their financial transaction data safely because there are security features similar to accuracy, except that before storing data, users must enter a special code as at the beginning when starting data recording. It can ensure security in recording financial statements and preventing data modification fraud.